Situational Leadership of Scholl Administrators According to the Perception of the Teachers in Demonstration Schools Affiliated with Autonomous University in Bangkok - Vatchanarat, Pattarawong; Sauphayana, Siriphong (Interdisciplinary Academic and Research Journal, 2023)
Regarding educational administration, school administrators are considered a significant driving force in finding ways to deal with every situation that arises. They must have a role in developing a successful organization. They must determine the vision, goals, and missions, and uses diverse strategies to create cooperation in planning various actions to achieve the desired goals in the changing situation continually and efficiently. The purposes of this research are to: (1) to study the situational leadership of school administrators according to the perception of the teachers in demonstration schools affiliated with autonomous universities in Bangkok (2) to compare the situational leadership of school administrators according to the perception of the teachers in demonstration schools affiliated with autonomous universities in Bangkok, based on level of education, age, and work experience. The sample group was 291 teachers using Cohen’s sample size table, specified at the statistical significance .05. Data were collected by questionnaires of 27 items with an Index of the item - Objective Congruence (IOC) valued at 0.80 - 1.00. Discrimination power was between 0.24-0.81 and reliability was at 0.921. Statistics used to analyze the data were frequency, percentage, mean, standard deviation, T-test for independent samples, and One Way ANOVA. When a statistically significant difference was found at .05, comparisons shall be made by Scheffe’s post hoc comparisons method. The findings reveal that: (1) The perception of the teachers on situational leadership of School administrators in demonstration schools affiliated with autonomous universities in Bangkok, both overall and in each aspect, was at a high level, based on the highest to the lowest of each aspect as follows: selling, participating, delegating and directing respectively. (2) The perception of the teachers, with different degrees, ages, and work experience, on situational leadership of school administrators in demonstration schools affiliated with autonomous universities in Bangkok, both overall and in each aspect, can be summarized as follows: (2.1) The perception of the teachers, with different degrees, on situational leadership of School administrators in demonstration schools affiliated with autonomous universities in Bangkok, both overall and each aspect, had no difference. (2.2) The overall perception of the teachers, at different ages, on situational leadership of School administrators in demonstration schools affiliated with autonomous universities in Bangkok was at the statistically significant level of .05. (2.3) The overall perception of the teachers, with different work experiences, on situational leadership of School administrators in demonstration schools affiliated with autonomous universities in Bangkok had no differences.